Role of nanoadditive blended biodiesel emulsion fuel on the performance and emission characteristics of diesel engine - S. Rajesh Kumar; P. Sai Chaitanya (Journal of Mechanical Engineering and Sciences, 2019)
An investigational research is carried out to found the performance and emission characteristics of a direct injection (DI) diesel engine with aluminium oxide nanoparticle additives in water and biodiesel blend. Palm methyl ester was produced by transesterification and blended with water. Aluminium oxide nanoparticles of 50 and 100 ppm in proportion are subjected to high-speed mechanical agitation followed by ultrasonication. The experimentations were conducted on a single cylinder DI diesel engine at a constant speed of 1500 rpm using different aluminium-oxide (AL2O3)-blended with emulsified biodiesel (PBD5%W+100ppm, PBD10%W+50ppm, PBD15%W+100ppm, PBD20%W+50ppm) and the outcomes were compared with those of neat diesel and Palm biodiesel. The experimental results indicated that brake thermal efficiency of PBD20%W+50 ppm and PBD+15%W+100ppm aluminium oxide was increased by 3-4% with 1.72% betterment in specific fuel consumption. Emissions of nitrogen oxide and hydrocarbon were reasonably lower than diesel fuel.